Trends of Mortality and Morbidity due to Ascariasis: A 14-year Analysis in a Tertiary Hospital in Bangladesh - Chowdhury, Tanvir Kabir; Chowdhury, Md Tameem Shafayat; Sharmin, Efat; Sayedin, Arif; Farooq , Md Abdullah Al (Bangladesh Journal of Infectious Diseases, 2023)
Background: Ascariasis is still a major public health concern and is termed as neglected tropical disease. There are surgical morbidity and mortality due to ascariasis. Objective: The general objective of the study was to analyze the trend of hospital admission and mortality from ascariasis at a tertiary government hospital in Bangladesh. Methodology: This was a retrospective chart review performed in the department of pediatric surgery at Chittagong Medical College Hospital, Chattogram, Bangladesh from a period of January 2006 to December 2019. Patients of 0 to 12 years of age who were admitted and diagnosed as intestinal or biliary ascariasis were analyzed for yearly trend for admissions, surgeries, and mortalities. Results: There were a total of 33,426 patients with various disease admitted and among them 2799 (8.67%) patients were diagnosed as intestinal ascariasis and 375(1.12%) patients were diagnosed as biliary ascariasis. Admission rate for intestinal ascariasis decreased from 15.87% in 2006 to 8.67% in 2019 and that for biliary ascariasis decreased from 1.87% to 0.98 %. The surgical load for intestinal obstruction decreased from 5.20% in 2006 to 1.09% in 2019 among all surgeries. Only one surgery was performed for biliary ascariasis. Mortality rate of ascariasis among all mortalities decreased from 20% to 5%. There was no death from biliary ascariasis. Conclusion: Surgical morbidity and mortality from intestinal ascariasis decreased over time but ascariasis is still causing loss of valuable lives. Bangladesh Journal of Infectious Diseases, June 2023;10(1):24-30